Charles W. Hack papers - Hack, Charles W.
Journals (1901-1903) kept by Hack while serving as a U.S. Army surgeon in the Philippines providing his impressions and experiences in Luzon, including Manila, and especially at Camp Vicars in the interior of Mindanao under the command of Major John J. Pershing. Hack describes social customs, relations between the U.S. Army and the local population, and public health problems. Also includes manuscripts of portions of the Koran in Arabic (circa 19th century) and of an excerpt of a Maranao oral literary epic, "Darangen," in Maranao written in Arabic script. Includes a summary of an assessment of the manuscripts by Richard J.H. Gottheil incorporating comments by "Kelekian," probably Dikran G. Kelekian. Also includes a listing of Moro artifacts exhibited in the American Museum of Natural History, New York, N.Y., in the 1920s.
U.S. Army officer and surgeon.
In part, typewritten transcripts.
Collection material in English, with Arabic and Maranao in Arabic script.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gottheil, Richard J. H. -- 1862-1936.; Kelekian, Dikran G., -- 1868-1951.; Pershing, John J. -- 1860-1948.; United States. -- Army -- Medical care; American Museum of Natural History; Epic poetry, Maranao; Material culture -- Philippines; Philippine literature; Public health -- Philippines; Luzon (Philippines) -- Description and travel; Manila (Philippines) -- Description and travel; Mindanao Island (Philippines) -- Description and travel; Philippines -- Description and travel; Philippines -- History -- Philippine American War, 1899-1902.; Philippines -- History -- 1898-1946.; Philippines -- Social life and customs; United States -- Armed Forces -- Philippines; Army officers; Surgeons